The Health Resources Allocation Model (HRAM) for the 21st century - Nicolas Maire; Michael Hegnauer; Dana Nguyen; Lucas Godelmann; Bernadette Peterhans; Axel Hoffmann; Don de Savigny; Marcel Tanner (Geospatial Health, 2012)
The Health Resources Allocation Model (HRAM) is an eLearning tool for health cadres and scientists introducing basic concepts of sub-national, rational district-based health planning and systems thinking under resources constraint. HRAM allows the evaluation of resource allocation strategies in relation to key outcome measures such as coverage, equity of services achieved and number of deaths and disability-adjusted life years (DALYs) prevented. In addition, the model takes into account geographical and demographic characteristics and populations’ health seeking behaviour. It can be adapted to different socio-ecological and health system settings.